Revealing Degradation Mechanisms in 3D/2D Perovskite Solar Cells under Photothermal Accelerated Ageing - Peng, Zijian; Vincze, Andrej; Streller, Fabian; Le Corre, Vincent Marc; Zhang, Kaicheng; Li, Chaohui; Tian, Jingjing; Liu, Chao; Luo, Junsheng; Zhao, Yicheng; Späth, Andreas; Fink, Rainer; et al. (Energy and Environmental Science, 2024)
Three-dimensional/two-dimensional (3D/2D) heterojunctions in perovskite solar cells exhibit excellent optoelectronic properties and enhanced stability under mild ageing conditions. However, their performance degrades drastically under harsh ageing conditions. This study reveals the intrinsic instability of mono-ammonium based 2D perovskites (2D-mono) under photo-thermal ageing, which decompose into PbI2 and metallic lead (Pb0). The structural collapse promotes vacancy formation and facilitates iodide migration to the anode. As a result, it triggers a redox reaction that reduces the transport layer’s mobility and doping concentration, leading to a significant increase in series resistance. Compared to mono-ammonium-2D structure, di-ammonium-2D (2D-di) based interfaces demonstrate superior structural stability and effectively block iodide migration into the transporting layer. However, blocking-induced uneven iodide distribution leads to interstitial defect formation in the 3D layer, exacerbating non-radiative recombination. To address it, we propose a strategical method by incorporating 2D-di in the 3D bulk instead of on the top surface, which effectively confines mobile ions within the grain and suppresses cation phase segregation. This optimization yields stable perovskite solar cells with an extrapolated operational T80 lifetime exceeding 560 hours under harsh conditions (85°C and 2-sun illumination